Self-Determination Theory SDT as educational and upbringing inspiration - Urszula Oszwa; Tomasz Knopik (Studia z Teorii Wychowania)
The Self-Determination Theory (SDT) is a universal macro-theory that comprehensively explains the mechanism of arousing and sustaining intrinsic motivation through six mini-theories. International research conducted for more than four decades indicates the applicability of the assumptions of SDT in educational practice, providing a multifaceted inspiration, both in the education and upbringing of the younger generation. The article presents the results of empirical explorations, verifying the theory's assumptions. In addition, tools developed on the basis of SDT that can be applied in the context of teaching-learning have been discussed. Potential challenges in the process of implementing the assumptions of SDT into the practice of education and upbringing have been also presented.